Efecto en los niveles de triglicéridos y colesterol en la sangre de cobayos (cavia cobayo) por medio de un régimen alimenticio a base de harina de chía (salvia hispanica) - Montoya Escobar, Jhoanna Fernanda (2016)
Chia is a pseudo cereal which has currently become a species of interest due to its high nutritional value. It has omega, proteins, soluble and insoluble fiber and antioxidants. Guinea pigs are animals that have helped both in animal exploitation and scientific research, thanks to its physiology. In the present study 30 male Guinea pigs were evaluated for 120 days in the fattening phase, originating in the experimental farm of the University of the Americas Nono - Quito, where they were assigned into two groups. The first group was the control group, given greens for food, the normal diet for Guinea Pigs. The second group were administered for 90 days a hyperlipemiante diet elevating the levels of lipids in cholesterol and triglycerides. Finally, after 120 days they were administered a diet enriched with Chia which reduced the levels of lipids of cholesterol and triglycerides. At the beginning of the study the first blood sample was taken to determine the lipid levels of cholesterol and triglycerides and to make sure they were at a normal level; this was repeated at 90 and 120 days. The method used for analyzing the blood chemistry was colorimetry. The design was completely random to obtain more accurate data. The conclusion is that eating a diet enriched with Chia helped the Guinea Pigs decrease lipid levels of cholesterol and triglycerides.